2015
DOI: 10.1186/s13071-014-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel sigma-like glutathione S-transferase from the giant panda parasitic nematode, Baylisascaris schroederi

Abstract: BackgroundBaylisascaris schroederi, an intestinal nematode of the giant panda, is the cause of the often fatal disease, baylisascariasis. Glutathione S-transferases (GSTs) are versatile enzymes that can affect parasite survival and parasite-host interactions and, are therefore, potential targets for the development of diagnostic tests and vaccines.MethodsIn this study, we identified a full-length cDNA that encoded a novel, secretory sigma-like GST (Bsc-GSTσ) from a B. schroederi-omic dataset. Following cloning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…An NCBI Blast search indicated that PpGST possessed a 'GST_N_Sigma_like domain' containing binding sites for glutathione (GSH) and a 'GST_C_like' domain containing a substrate-binding site. It has been reported that cytosolic GSTs contain thioredoxin-like domains with the topology bababba (Xie et al 2015). This secondary structure topology was also located in the PpGST identified in this study.…”
Section: Total Gst Enzyme Activitysupporting
confidence: 78%
See 3 more Smart Citations
“…An NCBI Blast search indicated that PpGST possessed a 'GST_N_Sigma_like domain' containing binding sites for glutathione (GSH) and a 'GST_C_like' domain containing a substrate-binding site. It has been reported that cytosolic GSTs contain thioredoxin-like domains with the topology bababba (Xie et al 2015). This secondary structure topology was also located in the PpGST identified in this study.…”
Section: Total Gst Enzyme Activitysupporting
confidence: 78%
“…The secondary structure of the PpGST consisted of a bababba motif in the N terminus (ranging from residues 5 to 84) and a nearly complete a helix motif (ranging from residues 91 to 204) in the C-terminus. These domain characteristics are highly similar to typical GST features (Xie et al 2015), suggesting that a responsive GST gene from P. polycephalum for nTiO 2 exposure was obtained.…”
Section: Total Gst Enzyme Activitysupporting
confidence: 63%
See 2 more Smart Citations
“…For instance, an antibody detection enzyme-linked immunosorbent assay (ELISA) employing a B. schroederi glutathione S-transferase antigen was established for the detection anti-B. schroederi serum antibody (IgG) in experimentally infected mice, with a sensitivity of 79.1% and a specificity of 82.0% (Xie et al, 2015a). However, such an assay has not yet been assessed for the diagnosis of baylisascariasis or B. schroederi infection in giant pandas.…”
Section: Diagnosismentioning
confidence: 99%